Strategi Pengendalian Pencemaran Air Sungai Gude Ploso Menggunakan Pemodelan QUAL2Kw - Putri Nadia Berliana; Hidayah, Euis Nurul (Jurnal Serambi Engineering, 2024)
This study focuses on the pollution of the Gude Ploso River in Jombang Regency, East Java Province, Indonesia, mainly caused by household and tofu industry waste. To control pollution, it is crucial to identify pollution sources, predict changes in water quality, and test the effectiveness of mitigation strategies. Our results show that several parameters in the Gude Ploso River exceed permissible limits, including total suspended solids (TSS), phosphate, and chemical oxygen demand (COD). Pollutant carrying capacity calculations indicate that phosphate and COD levels exceed the maximum carrying capacity at all sampling sites. Analysis using the STORET method indicates moderate levels of pollution with values of -30, -20, -21, and -21. Proposed mitigation strategies include monthly or quarterly monitoring of factories near the Gude Ploso River, conducting outreach and workshops for local communities to raise awareness about the state of the river, implementing phytoremediation at various points along the river, establishing environmental NGOs in the area, and conducting water flushing during dry periods. These strategies aim to reduce pollution in the Gude Ploso River, ensure the sustainability of its ecosystem, and provide a decent quality of life for the communities that rely on the river as a water resource.